Epidemiology of needlestick injury exposures among dental students during clinical training in a major teaching institution of China: A cross-sectional study - Jinwei Huang; Nan Li; He Xu; Yong Jiang; Chuanbin Guo; Tiejun Li; Zhigang Cai; Na An (Elsevier, 2022)
Background/purpose: Dental students are particularly vulnerable for needlestick injuries (NSI). However, the epidemiology of NSI exposures among Chinese dental students was rarely reported. The objectives of this study were to determine the prevalence of NSI among dental students in a major teaching institution of China, and to identify associated factors. Materials and methods: A self-administrated online questionnaire was developed based on previously published studies, and distributed to dental students of Class 2011-2015 recruited from Peking University School and Hospital of Stomatology. Results: Two hundred and sixty-eight dental students including 38.8% of males and 61.2% of females (response rate of 90.0%) completed the survey. Approximately 36.2% of the respondents had sustained at least one NSI. A total of 112 NSI cases were reported. The majority of NSIs were related to the procedures of local anesthesia administration (15.2%) and tooth cleaning or scaling (15.2%). Syringe needles, dental burs and ultrasonic chips were the most notorious devices. Statistical analysis showed significant distribution in NSI occurrence between July-September and October-December. The main cause was lapse in concentration (67.9%), followed by fatigue (22.3%). Up to 66.1% of the exposures occurred when the student was working alone, while only 10.7% with assisting. Unfortunately, 26.8% of the incidents were under-reported. Conclusion: Dental students are prone to needlestick injuries. The present study clearly reveals a need for increased awareness of NSI prevention among dental students. The quality of infection control education at dental teaching institutions is crucial and indispensable for reducing NSI exposures.